Modified Timed Up and Go Test for Tendency to Fall and Balance Assessment in Elderly Patients With Gait Instability - Soto-Varela, Andrés; Rossi-Izquierdo, Marcos; del-Río-Valeiras, María; Faraldo-García, Ana; Vaamonde-Sánchez-Andrade, Isabel; Lirola-Delgado, Antonio; Santos-Pérez, Sofía (Frontiers in Neurology, 2020)
Objective. To compare the results from the modified Timed Up and Go Test (TUG) with posturographic variables, the subjective perception of disability due to gait instability, and the number of falls in a sample of the elderly population with imbalance, to confirm that the TUG Test is a useful clinical instrument to assess the tendency to fall in individuals of this age group. Material and Methods. Cross-sectional study conducted in a tertiary university hospital, in 174 people aged 65 years or older with gait instability. Modified TUG Test was performed; time, step count and the need for support during the test were the analysed variables. They were compared with the number of falls, Computerized Dynamic Posturograpy scores, and questionnaires scores (Dizzines Handicap Inventory and a shortened version of the Falls Efficacy Scale-International). Results. The average time to complete the TUG Test was 21.24±8.18 seconds, and the average step count was 27.36±7.93. 102 patients (58.6%) required no support to complete the test, whereas the other 72 (41.4%) used supports. The time taken to complete the Test was significantly related with having or not having fallen in the previous year, with the scores of the questionnaires, and with various parameters of dynamic posturography. A higher percentage of patients who took more than 15 seconds had fallen in the previous year than those who took up to fifteen seconds to complete the test (P = 0.012; OR = 2.378; 95% CI (1.183, 4.780)). No significant correlation was found between the step count and the number of falls in the previous year, with falling during the test or not, or with being a single or a frequent faller. No relation was found between the need for supports and the number of falls, with having or not having fallen in the previous year, or with being a single or frequent faller. Conclusion. The modified TUG Test is in relation with the presence or absence of falls. Time is the essential parameter for analyzing the risk of falling and the 15-second threshold is a good value to differentiate elderly patients at high risk of falling.